"I did not finish school, school finished with me." Preparing today's children for 21st century life - Macharia, Kamau; Sabatini, Fabio (UNICEF CAO, 1997)
This paper draws on the recent situation analyses of children and their families in seven Eastern Caribbean countries to show how the education system in the sub-region finishes off with children well before they are equipped for either life or work, and even before their desire for learning has been exhausted. The heavily examination-oriented primary and secondary school system distorts the learning and teaching processes, and nullifies most of the intended benefits expected from the curriculum in the area of life and marketable skills, as well as psycho-social development and personal growth. It is suggested that Caribbean governments, the private sector, and development financial institutions must urgently move away from a principle of providing every child with primary education of dubious quality, while reserving decent secondary education for a minority of children, to endowing every child with a meaningful quality basic education that covers the entire period from birth to 16 years of age.
Keywords: Academic achievement